The Moderating Role of Gender: Collaboration of Brand Image, Service Quality, and Brand Trust in Increasing Student Loyalty Through Satisfaction - Abdillah, Yusuf; Qomariah, Nurul; Martini, Ni Nyoman Putu; Sobirov, Bobur (Universitas Brawijaya, Indonesia, 2025)
The increasing competition in higher education has prompted Muhammadiyah University of Jember to introduce the new program innovation, Recognisi Pembelajaran Lampau (RPL). To ensure the sustainability and growth of the program and contribute positively to society, understanding student loyalty is crucial for educational institutions. The purpose of this study is to examine the impact of brand image, service quality, and brand trust on student loyalty, with satisfaction serving as an intervening variable. This study method used is a quantitative survey with data collected through questionnaires. The respondents in this study were 144 students of the RPL program at Universitas Muhammadiyah Jember. Data analysis was performed using Structural Equation Modeling (SEM) with WarpPLS 8.0 software to test the relationships between the variables studied. The results show that brand image, service quality, and brand trust have a positive and significant influence on student satisfaction. Additionally, student satisfaction has a significant influence on student loyalty. Although brand image and service quality do not have a direct influence on loyalty, satisfaction as an intervening variable plays an important role in mediating the relationship between brand image, service quality, and brand trust with student loyalty. These findings provide practical implications for educational institution managers to improve brand image, service quality, and brand trust in order to enhance student satisfaction. By improving these three aspects, it is expected that students will be more loyal and have a higher commitment to their educational institution through mediated satisfaction. Through student loyalty, the marketing of educational programs can also be more efficient and effective for prospective new students.